Spectral tomographic analysis of Bremsstrahlung X-rays generated in a laser-produced plasma. (17th October 2016) - Rhee, Y.J.; Nam, S.M.; Peebles, J.; Sawada, H.; Wei, M.; Vaisseau, X.; Sasaki, T.; Giuffrida, L.; Hulin, S.; Vauzour, B.; Santos, J.J.; Batani, D.; et al.
Abstract: A new approach is proposed to analyze Bremsstrahlung X-rays that are emitted from laser-produced plasmas (LPP) and are measured by a stack type spectrometer. This new method is based on a spectral tomographic reconstruction concept with the variational principle for optimization, without referring to the electron energy distribution of a plasma. This approach is applied to the analysis of some experimental data obtained at a few major laser facilities to demonstrate the applicability of the method. Slope temperatures of X-rays from LPP are determined with a two-temperature model, showing different spectral characteristics of X-rays depending on laser properties used in the experiments.